Public Relations Strategies in Improving Brand Image and Institutional Competitiveness in the Digital Era - Zahro, Fatimatus; Diana, Eka (Electronic Journal of Education, Social Economics and Technology, 2025)
Competition among educational institutions in the digital age requires effective communication strategies to build a positive image and increase competitiveness. This study aims to analyze public relations strategies in shaping brand image and enhancing the competitiveness of MTs Walisongo 1 Maron amid the challenges of information technology development. The study employs a qualitative approach using a case study method, conducted through in-depth interviews, direct observation, and documentation of relevant parties within the madrasah environment. The results of the study indicate that public relations strategies at MTs Walisongo 1 Maron include the use of social media such as TikTok, Instagram, and Facebook to convey information and promotions, publish student achievements and school activities, and communicate directly with the community through print media and alumni involvement. The success of these strategies is supported by the school's A accreditation, student achievements in academic and non-academic fields, and the competitive quality of its graduates. However, the study also identified challenges such as limited human resources for content production, supporting facilities, and public relations staff working hours. Overall, public relations play a crucial role in building a positive institutional image and attracting community interest.